(untitled) (International Journal of Engineering and Computer Science, 2015)
Bolted joints are one of the most common elements in construction and machine design. A finite element model with three-dimensional solid elements was taken to investigate the bearing failure of stainless steel bolted connections under shear. This paper presents an extension of the finite element investigation onto the structural behaviour of stainless steel bolted connections, and three distinctive failure modes as observed in single lap and double lap shear tests are successfully modeled: bearing failure; shear-out failure; and net-section failure. Determine the material analysis of lap joints of the plates in accordance with the parametric optimization technique. Parametric optimization can be engaged by making a hole over the plate with several parameters. By analyzing the parametric study the net-section and shear-out failure are eliminated effectively. In bearing failure material optimization can be engaged by using stainless steel in accordance with the variation of loading conditions and parameters respectively.